Adverse Drug Reactions at Nonelective Hospital Admission in Children and Adolescents: Comparison of 4 Causality Assessment Methods. Issue 4 (June 2022) - Neininger, Martina Patrizia; Wehr, Raphaela; Kiesel, Lisa Marie; Neubert, Antje; Kiess, Wieland; Bertsche, Astrid; Bertsche, Thilo
Abstract : Objectives: This study aimed to compare assessment methods to determine adverse drug reactions (ADRs) at nonelective hospital admission in pediatric patients, to investigate the interrater reliability of assessment methods in pediatric care, and to analyze symptoms related to ADRs and (suicidal) drug intoxications. Methods: For 1 year, the medical records of nonelective patients admitted to a university pediatric department were evaluated for potential ADRs using 4 assessments methods by 1 experienced rater. Krippendorff α was calculated from a sample of 14 patients evaluated by 4 experienced raters to determine interrater reliability. Results: In 1831 nonelective hospital admissions, 63.4% (1161 of 1831) of patients had received at least one drug before admission. We found a potential causal relationship between drugs and symptoms documented at admission and thus potential ADRs according to Naranjo in 23.3% (271 of 1161) of those patients, World Health Organization - Uppsala Monitoring Centre (WHO-UMC) in 22.5% (261 of 1161), Koh in 21.7% (252 of 1161), and Begaud in 16.5% (192 of 1161). The probability rating of the potential causal relationships varied considerably between the methods (Naranjo-Begaud, P < 0.01; Naranjo-Koh, P < 0.001; Koh-Begaud, P < 0.01; Begaud-WHO-UMC, P < 0.01). Acceptable interrater reliability ( α ≥ 0.667) was only obtained for WHO-UMC ( α = 0.7092). The most frequently identified definite ADR was sedation in 1.5% of all nonelective patients with medication before hospital admission. In 1.2% (22 of 1831) of all nonelective admissions, we found drug intoxications with suicidal intent. Conclusions: The assessment methods showed a high variability in the determination of a potential causal relationship between drug and documented symptom, in the classification of the probability of ADRs, and suboptimal interrater reliability. Thus, their feasibility in pediatric patients is limited.